(untitled) (Research, Society and Development, 2022)
The present study contextualizes the certification process in grain storage unities by collecting data from the prevailing legal instruments (laws, decrees, normative ruling) that shelter the certification of the technical requirements itself. Therefore, this is a qualitative and explorative research made through a bibliographic revision of the literature related to the storage process, the biotechnology and legal science. This study also presents the main concepts related to the storage process, since the post-harvest moment until the final grain storage processes. Also, the technical requirements involving genetic modified food is mentioned, once they involve biotechnology and ethical questions regarding the transgenic grains and the implications involving the production process of those along with the environment, human health and animal damage prevention principle. In addition, the existence an interaction between the certificating processes and the legal science, the modernity and the contemplation of the technical requirements with the modern sciences. The results arise from the comparative analysis between the technical requirements exposed on the grain storage processes, according to the current law especially regarding the technical requirements that parametrize the certification of those storage unities.